Incidence of methicillin-resistant Staphylococcus aureus in wastewater and its survival after discharge from two hospitals in Akure, Nigeria - TOLULOPE EMORUWA; OLUFUMILOLA OMOYA (Nusantara Bioscience, 2024)
Abstract. Emoruwa T, Omoya O. 2024. Incidence of methicillin-resistant Staphylococcus aureus in wastewater and its survival after discharge from two hospitals in Akure, Nigeria. Nusantara Bioscience 16: 119-129. The prevalence of Methicillin-Resistant Staphylococcus aureus (MRSA), a silent infection-causing bacteria that is resistant to several antibiotics is rising in the population, increasing morbidity and mortality rates. The goal of this study was to find MRSA in hospital wastewater from the University of Medical Science Teaching Hospital and University Health Center, The Federal University of Technology Akure, Nigeria. Wastewater were collected from outlets in different wards, and pipe-borne water was collected as a control. The wastewater underwent bacteriological analysis using membrane filtration, identifying all the bacteria isolates. Zones of inhibition were interpreted to screen S. aureus isolates for antibiotic susceptibility. The mecA gene was molecularly identified in S. aureus isolates using bacterial DNA extraction and polymerase chain reaction. The plasmid profile and MRSA survivability at various pH, temperature, and salt concentrations were examined as well. The total bacterial counts in wastewater collected from UNIMEDTH and FUTA Health Center ranged from 49.72±0.86 CFU/100 mL (pipe-borne water) to 877.91±1.55 CFU/100 mL (Accident and Emergency ward) and 73.71±0.72 CFU/100 mL (pipe-borne water) to 422.05±1.55 CFU/100 mL (Wound treatment ward) respectively, while the total staphylococcal counts in UNIMEDTH and FUTA Health Center ranged from 0.00±0.00 CFU/100 mL (pipe-borne water) to 220.14±1.06 CFU/100 mL (Medical Laboratory Science Laboratory) and 1.02±0.11 CFU/100ml (pipe-borne water) to 60.11±0.11 CFU/100 mL (doctors’ station) respectively. Isolates of S. aureus were more resistant to ampiclox 10 (62.50%), oxacillin 7 (43.75%), zinnacef 10 (62.50%), and amoxicillin 8 (50.00%). The incidence of MRSA in hospital wastewater and its survival under different environmental conditions could present a public health challenge as the discharge of untreated wastewater could contaminate different water bodies.